Association between persistent high costs and chronic physical, mental and disability-related health conditions among community-dwelling Medicare-Medicaid dually eligible enrollees - Lirong Zhao Karyn Kai Anderson; Gerald Riley (Archives of Community Medicine and Public Health - Peertechz Publications, 2018)
Background: The 11.4 million Americans who receive both Medicare and Medicaid benefits constitute one of the nation's most vulnerable and costly populations. Objectives: We examine the relationship between persistently high costs (PHC) and physical, mental, and disability-related conditions among community-dwelling dully eligible enrollees. Research Design: Retrospective longitudinal study. Subjects: Community-dwelling beneficiaries who were continuously enrolled in Medicare and Medicaid fee-for-service 2007 through 2009. Measures: Beneficiaries in the top 10% of spending in all three study years were defined as having PHC. Chronic conditions were identified via CMS Chronic Condition Warehouse pre-defined variables. Results: Medicare and Medicaid collectively paid $77.7 billion for 1.46 million beneficiaries in the study from 2007 through 2009. Of these total expenditures, 39.3% were attributable to the 6.9% of dually eligible enrollees who were PHC. Medicaid accounted for 44.5% of total spending. Of the total Medicaid spending on dual enrollees, 67.9% was incurred by those individuals identified as PHC. An overwhelming 83.8% of PHC dually eligible enrollees were younger than 65 years. Beneficiaries with at least one disability-related condition were more likely to be PHC. In particular, beneficiaries with "intellectual disabilities and related conditions" were found to be 17 times more likely to be PHC compared to those without this condition, though this cost may be attributable to other concomitant health issues. Conclusion: Individuals with certain chronic conditions, especially disability-related conditions, tend to have persistently high costs over time. They may be particularly suitable candidates for interventions or payment models that promote more coordinated and efficient care. (250/250).